Autophagy-deficient Arabidopsis mutant atg5, which shows ultraviolet-B sensitivity, cannot remove ultraviolet-B-induced fragmented mitochondria. Issue 12 (25th November 2020) - Dündar, Gönül; Teranishi, Mika; Hidema, Jun
Abstract : UV-B led to the inactivation and fragmentation of mitochondria, which are removed by mitophagy. Mitophagy might be one of the important repair mechanisms for UV-B-induced damage in Arabidopsis . Abstract : Mitochondria damaged by ultraviolet-B radiation (UV-B, 280–315 nm) are removed by mitophagy, a selective autophagic process. Recently, we demonstrated that autophagy-deficient Arabidopsis thaliana mutants exhibit a UV-B-sensitive phenotype like that of cyclobutane pyrimidine dimer (CPD)-specific photolyase (PHR1)-deficient mutants. To explore the relationship between UV-B sensitivity and autophagy in UV-B-damaged plants, we monitored mitochondrial dynamics and autophagy in wild-type Arabidopsis (ecotype Columbia); an autophagy-deficient mutant, atg5 ; a PHR1-deficient mutant, phr1 ; an atg5 phr1 double mutant; and AtPHR1-overexpressing (AtPHR1ox) plants following high-dose UV-B exposure (1.5 W m −2 for 1 h). At 10 h after exposure, the number of mitochondria per mesophyll leaf cell was increased and the volumes of individual mitochondria were decreased independently of UV-B-induced CPD accumulation in all genotypes. At 24 h after exposure, the mitochondrial number had recovered or almost recovered to pre-exposure levels in plants with functional autophagy (WT, phr1, and AtPHR1ox), but had increased even further in atg5 . This suggested that the high dose of UV-B led to the inactivation and fragmentation of mitochondria, which were removed by mitophagy activated by UV-B. The UV-B-sensitive phenotype of the atg5 phr1 double mutant was more severe than that of atg5 or phr1 . In wild-type, phr1, and AtPHR1ox plants, autophagy-related genes were strongly expressed following UV-B exposure independently of UV-B-induced CPD accumulation. Therefore, mitophagy might be one of the important repair mechanisms for UV-B-induced damage. The severe UV-B-sensitive phenotype of atg5 phr1 is likely an additive effect of deficiencies in independent machineries for UV-B protection, autophagy, and CPD photorepair.